Fuzzy multicriterial methods for the selection of IT-professionals - Jabrayilova, Zarifa Gasim (International Journal of Intelligent Systems and Applications in Engineering, 2015)
This paper presents the solution of issues related to selection based on evaluation of demand set forth to IT specialists, to develop appropriate decision support system. In this case problem is reduced to multicriterial task of decision making, functioning in a fuzzy environment.We propose criteria estimation method allowing regulation and selection of the best alternative according to the scenario appropriate to the requirements of the decision making person, at a current time. For realization of abovementioned task on the basis of fuzzy logic methods we propose methods of expert knowledge processing of the importance criteria and their characterizing factors.